Imperfect/I'm perfect: bodies/embodiment in post-secondary and elementary settings. (2nd January 2017) - Winters, Kari-Lynn; Code, Mary
ABSTRACT: Using researched perspectives of bodies and embodiment, alongside dramatic structures, where bodies are foregrounded, this article looks closely at bodies and embodiment inside of school settings. Specifically, it investigates a community in Southern Ontario and the perceived, affective, relational, and critical ways that study participants story their identities about their bodies. Findings suggest that body image itself (i.e. how youth perceive their bodies) and embodiment (i.e. how youth use their bodies for communication and learning) are vital but sometimes invisible topics in today's school settings, where bodies are continually interpreted, admired, shamed, moved, rejected, and positioned. Though drama and other subjects like the arts focus on embodied ways of knowing and offer unique opportunities for learning, they can also hold unique challenges in school settings.